CRITICAL ANALYSIS OF VALUE CHAIN: A CASE OF MANGO PROCESSING VARIETIES IN CHITTOOR DISTRICT OF ANDHRA PRADESH - R. BINDU SOWMYA *, N. T. KRISHNA KISHORE, T. LAKSHMI and SHAIK NAFEEZ UMAR, (The Journal of Research ANGRAU, 2022)
In India, Andhra Pradesh leads in thearea under mango with 14.72%, while UttarPradesh leads in production of mango with23.47% with highest productivity, followed byAndhra Pradesh with 22.63% i.e., 4.6 milliontonnes, and then Karnataka, Bihar, Gujarat,Tamil Nadu, Odisha, West Bengal, Jharkhand,and Maharashtra. In Andhra Pradesh, Chittoordistrict contributes production of 15.5 lakhtonnes covering 1.12 lakh ha.Of these 26000ha have table variety mango trees such asBenishan (Banginapalle), Neelum, Dashehari,Kesar, Himayath etc. While 86000 ha have theTotapuri mango variety, which is mainly usedby the industry to make pulp. The industry isconcentrated in Chittoor district and is a mainhub for the export of mango pulp to differentnations. (APEDA, 2022).Value chain refers to“the set of actors (private, public, and serviceproviders) and the sequence of value-addingactivities involved in moving a product fromproduction to the final consumer,” in agriculturethey can be thought as is a “farm to fork” setof processes and flows. Farmers, inputsuppliers, private traders, processors,exporters, and consumers are all a part ofmango value chain. (Nandika and Jayasree,2017). As a result, the following objectives wereset for the research:to identify major actors andtheir roles, and major constraints faced bythem in value chain of mango, and mappingand analysing the agri value chains for majormango varieties grown in Chittoor (RekhaPriyadarshini, 2015).